Socio-demographic and socioeconomic differences in tobacco use prevalence among Indian youth - Deepti Nagrath; Manu R. Mathur; Rakesh Gupta; Sanjay P. Zodpey (Preventive Medicine Reports, 2019)
The study aims to assess the association between socio-demographic factors such as age, gender, area of residence, father's education, and standard of living and the likelihood of tobacco use in adolescence.We conducted secondary data analysis on a large scale cross-sectional study comprising of 1386 adolescents, living in regions representative of three different socioeconomic positions in New Delhi.Data was collected through clinical oral examination and interviewer-administered questionnaire.Multiple logistic regression analysis with an unadjusted model for assessing the association between the respective explanatory variable and ever tobacco use. Sequential models were adjusted for confounders as well as the other explanatory variables.The number of tobacco users was 185 (13%). Gender wise tobacco use shows significant (P = 0.001) difference between girls vs. boys; the girls are about 40% less likely to use tobacco than boys (OR = 0.58, 95% CI = 0.42–0.80). Among socio-economic classes, residents of resettlement colonies were twice as likely to use tobacco as middle/upper middle class residents (OR = 2.26, 95% CI = 1.45–3.53). Adolescents with fathers educated up to the primary or secondary levels were almost twice likely to have used tobacco than those with fathers educated till graduation or above (OR = 2.08 95% CI = 1.30–3.34 vs. OR = 2.24, 95% CI = 1.43–3.51, respectively). Significant (P = 0.001) difference in tobacco use among adolescents was also observed based on their standard of living.A significant association exists in terms of area of residence, father's education, and standard of living. Keywords: Adolescents, Tobacco, Area of residence, Inequalities, Social gradient